Guidelines for developing a learning organization of the Office of The Permanent Secretary, Ministry of Education - Hastheithong, Napaporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This research aimed to: 1) compare the level of learning organization of Office of Permanent Secretary, Ministry of Education as classified by personal factors; 2) study factors affecting the learning organization of Office of Permanent Secretary, Ministry of Education in the aspects of proper structure, educational technology, teamwork and network system, and knowledge construction and transfer; and 3) identify the guidelines for development of learning organization of Office of Permanent Secretary, Ministry of Education. The research sample was 1) 245 personnel of the Office of Permanent Secretary, Ministry of Education, derived by stratified random sampling. The instrument used for data collection was a questionnaire constructed by the researcher. Data were analyzed with percentage, mean, standard deviation, t-test, one-way analysis of Variance, least significant difference, correlation coefficient, multiple regression, and content analysis. 2) The 10 key informants consisted of supervisors, group leaders, and division directors of Office of Permanent Secretary, Ministry of Education, who voluntarily joined the research. They were selected by purposive sampling. The research results revealed that: 1. The level of learning organization of Office of Permanent Secretary, Ministry of Education as perceived by personnel with different genders, ages, status, positions, work experiences and chain of command was not different. However, the difference was found among personnel with overall education level with significant difference at .05 levels. 2. Regarding the factors affecting the learning organization, the aspects of knowledge construction and transfer (b=0.36), proper structure (b=0.19), and teamwork and network system (b=0.17) significantly affected the learning organization with predictive power of 81 percent. The equation was as follows: Y = 1.01 + 0.19**(X1) + 0.04(X2) + 0.17**(X3) + 0.36**(X4). 3. The guidelines for development of learning organization of Office of Permanent Secretary, Ministry of Education, were the administrators should: give importance, support, and motive the personnel to realize learning organization being; develop new concepts, plan for organization development, and monitor the implementation continuously; apply technology to develop learning organization being based on personnel suitability, transfer knowledge via network, build information technology system to certify the development, and add more learning channels for new innovations; develop personnel and adjust personnel’s behaviors, create vision for personnel development, encourage personnel to be more enthusiastic to self-development of and life-long learning, and promote cooperative learning and knowledge and experience transfer. These will lead to mutual working paradigm and systematic knowledge collection and management. Article history: Received 10 September 2019 Revised 1 October 2019 Accepted 4 October 2019 SIMILARITY INDEX = 0.00 %